Impact of Intraoperative Prognostic Factors on Urinary Continence Recovery Following Open and Laparoscopic Radical Prostatectomy - Boris M. Kajmakovic; Milos Petrovic; Petar R. Bulat; Uros Bumbasirevic; Bogomir Milojevic; Predrag Nikic; Aleksandar Janicic; Otas Durutovic; Bojan Cegar; Adi Hadzibegovic; Sanja Ratkovic; Zoran M. Dzamic (Medicina)
Background and Objectives: Radical prostatectomy (RP) stands as the predominant instigator of postoperative stress urinary incontinence. Techniques such as the preservation of the neurovascular bundles, bladder neck preservation, and ensuring longer postoperative urethral length have shown positive impacts on continence. The posterior reconstruction is another method that aids in early continence recovery. Anterior suspension as simulator of puboprostatic ligaments is another factor. Materials and Methods: This study was conducted in the Clinic of Urology, University Clinical Center of Serbia, between December 2014 and January 2020, employing a prospective, non-randomized comparative design. Data were meticulously gathered from 192 consecutive patients. The process of regaining continence was monitored at intervals of 1, 3, 6, 12, and 24 months after surgery. The main criterion for assessing the level of urinary continence was the number of pads used daily. Results: The distribution of overall continence rates in the BNP vs. no-BNP group at 3, 6 and 12 months was 86% vs. 60% (p < 0.0001), 89% vs. 67% (p < 0.0001), 93% vs. 83% (p = 0.022). Continence rates in non-posterior reconstruction group (10%, 22%, 34%, and 54% at 1, 3, 6, and 12 months) were statistically significantly lower (p < 0.0001). The patients who underwent urethral suspension exhibited significantly higher rates of overall continence at 1 mo (73% vs. 29%, p < 0.0001), 3 mo (85% vs. 53%, p < 0.001), 6 mo (89% vs. 62%, p < 0.0001), 12 mo (95% vs. 76%, p < 0.0001), and 24 mo (93% vs. 81%, p = 0.007). Patients who underwent urethral suspension had a four-fold greater likelihood of regaining continence (p = 0.015). Conclusions: Patients who underwent urethral suspension or BNP or posterior reconstruction had higher continence rates. Only the urethral suspension was found to be a significant prognostic factor of continence recovery.